2012
DOI: 10.1007/s11099-012-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving growth, flower yield, and water relations of snapdragon (Antirhinum majus L.) plants grown under well-watered and water-stress conditions using arbuscular mycorrhizal fungi

Abstract: The influence of arbuscular mycorrhizal (AM) fungus Glomus deserticola (Trappe and John) on plant growth, nutrition, flower yield, water relations, chlorophyll (Chl) contents and water-use efficiency (WUE) of snapdragon (Antirhinum majus cv. butterfly) plants were studied in potted culture under well-watered (WW) and water-stress (WS) conditions. The imposed water stress condition significantly reduced all growth parameters, nutrient contents, flower yield, water relations, and Chl pigment content and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
84
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(108 citation statements)
references
References 65 publications
21
84
0
3
Order By: Relevance
“…On the other hand, mycorrhizal hyphae would extend soil water depletion zones, thus, providing mycorrhizal roots more access to available soil water (Wu et al, 2013;Zou et al, 2015). Furtherly, mycorrhizal hyphae enhance the ratio of below-ground absorptive surface to leaf area (Asrar et al, 2012). This may explain that in the present study, a significantly higher leaf Ψ was found in AM trifoliate orange than in non-AM trifoliate orange exposed to WW and DS (Fig.…”
Section: Leaf Water Potential (Leaf ψ )mentioning
confidence: 53%
“…On the other hand, mycorrhizal hyphae would extend soil water depletion zones, thus, providing mycorrhizal roots more access to available soil water (Wu et al, 2013;Zou et al, 2015). Furtherly, mycorrhizal hyphae enhance the ratio of below-ground absorptive surface to leaf area (Asrar et al, 2012). This may explain that in the present study, a significantly higher leaf Ψ was found in AM trifoliate orange than in non-AM trifoliate orange exposed to WW and DS (Fig.…”
Section: Leaf Water Potential (Leaf ψ )mentioning
confidence: 53%
“…In addition, in potted inoculated plants, AM-colonized roots can reach a maximum level of exploration of the substrate earlier than noninoculated plants (Berruti et al, 2016). Differences from previous literature data, showing that C leaf either did not differ between AM and noncolonized plants under drought or was higher (less negative) in the presence of the AM fungus (Porcel et al, 2004;Khalvati et al, 2005;Asrar et al, 2012), could be due to diverse experimental designs, growth conditions, and plant/ fungus combinations. Indeed, it was reported recently that the cooperation in AM interactions is related to the partners involved in the symbiosis and depends on several factors, including environmental conditions, the acquisition of surplus resources, and functional diversity (Walder and van der Heijden, 2015).…”
Section: Impact Of Mycorrhizal Symbiosis On Tomato Physiological Perfmentioning
confidence: 59%
“…Information on the effects of AM fungi on flowering is disparate. In particular, it has been shown that AM fungi usually increase flower amount, the number of flowering plants in a stand, or flowering earliness (Schenck and Smith 1982;Gaur et al 2000;Scagel 2004;Perner et al 2007;Bunn et al 2009;Asrar et al 2012;Bona et al 2015). However, it also has been found that AM fungi can have no effects on flowering (Linderman and Davis 2004), delay its onset, or increase its duration (Schenck and Smith 1982;Dubský and Vosátka 2000;Saia et al 2014a;Jin et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the role of AM symbiosis in flowering date and flower amount, flowers frequently being the plant organ with highest SM concentration and content, is fragmented. It has been shown that AM fungi can induce earlier (Usha et al 2005;Bona et al 2015) or delayed flowering (Nowak 2004;Saia et al 2014a) and either increase, reduce, or have no effect on flower number (Gaur and Adholeya 2005;Perner et al 2007;Asrar et al 2012;Bona et al 2015). Such effects differed among host plants, AM species or consortium used, nutrient availability, and other growth conditions.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%